Analysis of the threshold range of ROS concentration in winter rapeseed of the Brassica napus type - Qi, Weiliang; Sun, Wancang (Frontiers in Plant Science, 2025)
The threshold range of reactive oxygen species (ROS) concentration remains a critical challenge and focal point in future research concerning its influence on the growth and development of both beneficial and harmful plants. This study demonstrates that as the concentration of hydrogen peroxide (H2O2) increases from 0.0% to 0.6%, the seed germination rate gradually rises. At 0.6% H2O2, the germination rate peaks at 94.67%, accompanied by the maximum activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT). However, with further increases in H2O2 concentration (0.7% – 1.3%), the seed germination rate and antioxidant enzyme activity gradually decline, while the levels of superoxide anion (O2-) and H2O2 accumulate progressively. This suggests that higher H2O2 concentrations impair the ROS scavenging capacity in cabbage-type rapeseed, leading to increased ROS production and subsequent inhibition of growth and development. At half-lethal H2O2 concentrations (1.4%–1.5%), the seed germination rate before rehydration is significantly reduced to 10.97% and 9.03%, respectively, but can recover to approximately 50% after rehydration. H2O2 concentrations exceeding 2.2% are lethal, resulting in a 0% seed germination rate both before and after rehydration; notably, the post-rehydration germination rate remains below 10%. At these concentrations, the levels of O2-, SOD, POD, and CAT decrease to their minimum values, indicating that high exogenous H2O2 concentrations induce cell death, which in turn suppresses ROS production and inactivates ROS-scavenging enzyme activity. Consequently, cellular osmotic potential increases, leading to the accumulation of high concentrations of exogenous H2O2 within cells.